Broadband Excitation from X-Ray to UV for Afterglow Emission in Monodisperse Lanthanide-Doped Nanoengineered Molecular Nanotransducers - Guan, Shuaimeng (Advanced materials (Deerfield Beach, Fla.), 2025)
© 2025 Wiley‐VCH GmbH.